Lipid transformation during postmortem chilled aging in Mongolian sheep using lipidomics. (30th March 2023) - Zhang, Min; Su, Rina; Corazzin, Mirco; Hou, Ran; Zhang, Yue; Sun, Lina; Hu, Guanhua; Dou, Lu; Guo, Yueying; Su, Lin; Zhao, Lihua; Jin, Ye
Highlights: The chilled aging time was closely related to the lipid content and species. GP and FA were the main differential lipid classes during chilled aging. 48 h of postmortem chilled aging was the turning point for lipid transformation. Hydrolase activity and oxidation degree might be responsible for lipid changes. Glycerophospholipid metabolism and thermogenesis are the major aging pathways. Abstract: This present study aimed to investigate the effects of postmortem chilled aging on lipid and molecular transformation mechanisms in Mongolian sheep. UPLC-ESI-MS/MS was used to identify 812 lipids in Mongolian sheep within four days of chilled aging. Using multivariate analysis, 95 significant differential lipids were identified. The levels of phosphatidylcholine, phosphatidylinositol, and certain free fatty acids were observed to rise significantly, while other phospholipids and acylcarnitines showed a downward trend. In addition, levels of most of the lysophospholipids increased significantly in the early postmortem period; however, their levels did not alter significantly after 48 h. The Kyoto encyclopedia of genes and genomes pathway analysis revealed that these differential lipids are primarily involved in glycerophospholipid metabolism, linoleic acid metabolism, arachidonic acid metabolism, and thermogenesis. Our results have important implications in terms of understanding lipid transformation and changes in meat quality during postmortem chilled aging in Mongolian sheep.